Wage Rigidity in a Competitive Incomplete Contract Market - Fehr, Ernst; Falk, Armin (Journal of Political Economy, 1999)
Do employers and workers underbid prevailing wages if there si unemployment? Do employers take advantage of workers' underbidding by lowering wages? Do employers take advantage of workers underbidding by lowering wages? We hypothesize that under conditions of incomplete labor contracts, wage levels may positively affect workers' propensity to cooperate. This, in turn, may prevent firms from underbidding or accepting the underbidding of workers. Experimental double auctions conducted for the purpose of examinating these hypotheses yield the following results: (i) Workers' underbidding is very frequent, but employers refuse to accept workers' low wage offers in markets with complete labor contracts, employes accept and actively enforce wages close to the competitive level. (ii) Workers' effort is positively related to the wage level. Therefore over their effort level. This holds true even in the presence of explicit performance incentives.